2021
DOI: 10.5194/acp-21-2407-2021
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of intermediate-volatility and semi-volatile organic compounds from domestic fuels used in Delhi, India

Abstract: Abstract. Biomass burning emits significant quantities of intermediate-volatility and semi-volatile organic compounds (I/SVOCs) in a complex mixture, probably containing many thousands of chemical species. These components are significantly more toxic and have poorly understood chemistry compared to volatile organic compounds routinely quantified in ambient air; however, analysis of I/SVOCs presents a difficult analytical challenge. The gases and particles emitted during the test combustion of a range of domes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 106 publications
8
29
4
Order By: Relevance
“…The maximum error in this calibration approach was shown to be 21 % (Taipale et al, 2008). Peak assignment was assisted with results reported by previous burning studies and references therein (Brilli et al, 2014;Stockwell et al, 2015;Koss et al, 2018). The results may also contain other indistinguishable structural isomers not mentioned here.…”
Section: Ptr-tof-msmentioning
confidence: 57%
See 4 more Smart Citations
“…The maximum error in this calibration approach was shown to be 21 % (Taipale et al, 2008). Peak assignment was assisted with results reported by previous burning studies and references therein (Brilli et al, 2014;Stockwell et al, 2015;Koss et al, 2018). The results may also contain other indistinguishable structural isomers not mentioned here.…”
Section: Ptr-tof-msmentioning
confidence: 57%
“…Most species of similar functionality tracked each other. Stockwell et al (2015) demonstrated that benzene, phenol and furan could act as tracers for aromatic, phenolic and furanic species released from biomass burning. Figure 5a shows that heavier, more substituted phenolics appeared to be released at cooler temperatures.…”
Section: Ptr-tof-ms Concentration Time Series Analysismentioning
confidence: 99%
See 3 more Smart Citations